2012
DOI: 10.5194/cpd-8-2041-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cascading climate effects and related ecological consequences during past centuries

Abstract: The interface between climate and ecosystem structure and function is incompletely understood, partly because few ecological records start before the recent warming phase. Here, we analyse an exceptional 100-yr long record of the great tit (<i>Parus major</i>) population in Switzerland in relation to climate and habitat phenology. Using path analysis, we demonstrate an uninterrupted cascade of significant influences of the large-scale atmospheric circulation (North-Atlantic Oscillation, NAO, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Hatching date is constrained by laying date, clutch size and incubation date (Godfray et al 1991;Visser et al 2004). Synchrony between individual behavior and suitable timing of breeding is determined by environmental clues (Parmesan 2006;Visser et al 2006;Sih et al 2011) such as temperature Charmantier et al 2008;Naef-Daenzer et al 2012), light (Dominoni et al 2013), and date of bud burst . Moreover, global temperature increases in early spring have advanced the phenology of birds over the last few decades (Both and Visser 2001;Both et al 2004;Visser et al 2006;Both and te Marvelde 2007;Møller et al 2010;Porlier et al 2012;Charmantier and Gienapp 2014;Dunn and Møller 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hatching date is constrained by laying date, clutch size and incubation date (Godfray et al 1991;Visser et al 2004). Synchrony between individual behavior and suitable timing of breeding is determined by environmental clues (Parmesan 2006;Visser et al 2006;Sih et al 2011) such as temperature Charmantier et al 2008;Naef-Daenzer et al 2012), light (Dominoni et al 2013), and date of bud burst . Moreover, global temperature increases in early spring have advanced the phenology of birds over the last few decades (Both and Visser 2001;Both et al 2004;Visser et al 2006;Both and te Marvelde 2007;Møller et al 2010;Porlier et al 2012;Charmantier and Gienapp 2014;Dunn and Møller 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In rural and natural habitats, egg laying of birds is delayed by cold prelaying temperatures (Charmantier et al 2008;Visser et al 2009;Naef-Daenzer et al 2012;Schaper et al 2012;Chmielewski et al 2013;Vatka et al 2014), at high latitudes (Mainwaring et al 2012;Ruffino et al 2014), or when bud burst date is delayed (Naef-Daenzer et al 2012). Moreover, the both effects of latitude (Mainwaring et al 2012) and bud burst (Schaper et al 2011;Visser et al 2012) seem to be related to temperature effects.…”
Section: Introductionmentioning
confidence: 99%
“…Influences of large-scale climate processes in ecology are well established [ 1 7 ] and have been used to examine historical events as well as to predict future ones. For example, in an analysis of great tit population dynamics spanning 100 years in Switzerland [ 11 ], breeding phenology and performance were linked to a chain of events starting with global climate processes (measured using winter/late spring NAO indices and the North Sea–Caspian Pattern), proceeding through local weather patterns (rainfall and temperature) and habitat phenology (beech bud burst) and ending with individual life histories. A number of studies have also reported time-lags in ecological responses to the NAO, but these are usually driven by biotic rather than abiotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…For western and northern Europe and eastern North America, the North Atlantic Oscillation (NAO) is one such climate process influencing both marine and terrestrial ecosystems [ 6 , 7 ]. In particular, the NAO winter index (NAO WI) (based on the difference in normalised sea pressures between the Azores and Iceland for December to March [ 8 , 9 ]) has been linked to breeding phenology, reproductive success and survival in a wide range of taxa including birds, mammals and fish [ 6 , 10 , 11 ]. In northern Europe, positive values of the index are associated with warmer, wetter winters and negative values with colder, drier ones, while the reverse is the case in North America (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of embryos to temperatures outside the optimal range can be lethal or detrimental (Gluckman et al 2007, Durant et al 2013. For example, fledging success in great tits over a hundred-year period was negatively influenced by average January to April environmental temperatures (Naef-Daenzer et al 2012).…”
Section: Marie Vaugoyeau Sandrine Meylan and Clotilde Biardmentioning
confidence: 99%